Effects of Foliar Application of Magnesium Fertilizer on Photosynthesis and Growth in Grapes - Rui Bai; Huan Liu; Yifei Liu; Jean Wan Hong Yong (Agronomy)
Efforts to increase grape yields have focused on using nitrogen, phosphorus, and potassium fertilizers, often causing unintended magnesium (Mg) deficiencies. To overcome Mg deficiency, different concentrations of MgSO4·7H2O (0, 1, 2, 3, 4 mM) and GABA (2.5 mM), as foliar sprays, were applied during the fruit enlargement and color transition stages. Key physiological parameters such as leaf growth, photosynthesis, and chlorophyll fluorescence were assessed. Interestingly, foliar Mg application increased the key physiological parameters, with the 3 mM treatment (M3) delivering the best improvement. Compared to the control, the M3 treatment increased dry weight and leaf area by 35.9% and 37.2%, respectively. Specifically, the foliar Mg application (M3) improved the photosynthesis (Pn), transpiration (Tr), and stomatal conductance (gs) of leaves when compared to the control. Additionally, the foliar Mg application improved the PSII photosynthetic efficiency, electron yield, and electron transport rates, following the order M2 > M3 > M1 > M0 > M4. This study demonstrated the essential role of foliar-applied Mg, with GABA, in improving grape physiology. Interestingly, the curve-fitting analysis of foliar Mg concentration and grape yield identified 2.14 mM of Mg as the optimal concentration for promoting grape growth.